2020
DOI: 10.1038/s41437-020-00357-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing whole-genomic prediction for autotetraploid blueberry breeding

Abstract: Blueberry (Vaccinium spp.) is an important autopolyploid crop with significant benefits for human health. Apart from its genetic complexity, the feasibility of genomic prediction has been proven for blueberry, enabling a reduction in the breeding cycle time and increasing genetic gain. However, as for other polyploid crops, sequencing costs still hinder the implementation of genome-based breeding methods for blueberry. This motivated us to evaluate the effect of training population sizes and composition, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 59 publications
(111 reference statements)
4
37
0
Order By: Relevance
“…In a recent study, we demonstrated that such numbers are quite conservative for genomic prediction. By combining a simple genetic parametrization (ratio) and low-to-mid sequencing depth (6x-12x), we achieved similar predictive accuracies as higher-depths for blueberry traits with different genetic architectures (de Bem Oliveira et al, 2020). Similar results are also reported by Zheng et al (2020).…”
Section: Filling the Gaps: Phenotypic And Genotypic Selection In The supporting
confidence: 76%
See 2 more Smart Citations
“…In a recent study, we demonstrated that such numbers are quite conservative for genomic prediction. By combining a simple genetic parametrization (ratio) and low-to-mid sequencing depth (6x-12x), we achieved similar predictive accuracies as higher-depths for blueberry traits with different genetic architectures (de Bem Oliveira et al, 2020). Similar results are also reported by Zheng et al (2020).…”
Section: Filling the Gaps: Phenotypic And Genotypic Selection In The supporting
confidence: 76%
“…About half of the capture-seq genotyping probes that were originally developed based on a draft genome assembly were discarded afterwards based on the high-quality genome, without compromising genetic association and ge nomic prediction analyses (Benevenuto et al , 2019). We also explored additional optimizations to reduce costs, regarding the number of individuals per family, number of markers, and sequencing depth (de Bem Oliveira et al , 2020). Moreover, new genomics methods and tools have been developed in the last decade for the polyploid community, including allele dosage estimation, haplotype reconstruction, and the use of different relationship matrices (Bourke et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic (Elshire et al 2011), statistical (Meuwissen et al, 2001; Gianola et al, 2009), and computational advances have allowed significant increases in genetic gain by applying genomic prediction (GP) in breeding programs across several species (e.g., Hayes et al, 2009; Fe et al, 2015, 2016; Gezan et al, 2017; de Bem Oliveira et al, 2020; Amadeu et al, 2020). Taking advantage of the ever-reducing cost of molecular markers (Wetterstrand, 2020), the concept of GP was derived (Meuwissen et al, 2001) as an alternative method to marker-assisted selection (MAS).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneer studies implementing GP in plants were performed in mayor crop species with traditional hybrid selection such as maize (Massman et al, 2013; Combs and Bernardo, 2013) and trees (Resende et al, 2012; Kumar et al, 2012), or variety selection in self-pollinating species (Poland et al, 2012). Genomic prediction showed to be a powerful tool to achieve higher genetic gain in plant breeding in many other species (Crossa et al, 2017; Lara et al, 2019; de Bem Oliveira et al, 2020; Esfandyari et al, 2020). Large commercial breeding companies have been applying GP; however, the success of the process depends strongly on the species architecture and the breeding program scheme (Xu et al, 2020; Voss-Fels et al, 2019)…”
Section: Introductionmentioning
confidence: 99%